CANDRASANGKALA DI PURA TIRTHA EMPUL TAMPAKSIRING, KABUPATEN GIANYAR - dewa gede yadhu basudewa (Journal Social and Humaniora, 2017)
Candrasangkala in the form of the composition of the picture (chronogram) engraved sun, elephants, candi bentar, and the dragon is found on the walls of sacred buildings Tepasana in Tirtha Empul temple Tampaksiring. The composition of the image is analyzed using qualitative analysis to describe and classify into candrasangkala assessment system uses watek and guru. Based on the analysis obtained a grading system, namely: the sun has a value of 1, the elephant has a value of 8, candi bentar has a value of 9, and the dragon has a value of 8 to get an arrangement of year numbers 1898 ?aka or 1976 AD. ?aka year is estimated as a warning sign/events on completion of restoration of sacred buildings in the form of old building (bebaturan) named Tepasana in Tirtha Empul temple Tampaksiring. Keywords: candrasangkala, tirtha empul temple